Abnormal twinning in goat: a review - Pourlis, A; Papakonstantinou, G; Papatsiros, V (Journal of the Hellenic Veterinary Medical Society, 2024)
A survey of congenital malformations relating to abnormal caprine twins was carried out. According to the degree, sites, and angle of fusion, they have various external variations and are classified as free asymmetric, conjoined symmetric or asymmetric twins (heteropagus or parasitic twins). The aim was to describe and summarize these defects. Among the recorded abnormal twining in goats, several common defects relate to thoraco-omphalopagus. A series of dicephali and diprosopus monsters have also been registered. At last, cases of free asymmetrical twins have been reviewed. There is also a report of a case of unequal conjoined–parasitic twins. The pathogenetic mechanisms of this condition, frequently reported in veterinary practice, are discussed. However, the etiopathogenesis of imperfect twins remains puzzling. The importance of embryonic duplications is commonly associated with dystocia. The manuscript finally introduces a framework of an essential national registry for the malformed companion animals.